2014
DOI: 10.1097/phh.0000000000000034
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Vaccination Rates in Children With Sickle Cell Disease

Abstract: Barriers to completing age-appropriate recommended pneumococcal immunizations should be identified and addressed to further reduce invasive pneumococcal disease in this high-risk patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
4
14
0
Order By: Relevance
“…A case-control study of pneumococcal vaccine adherence (PCV7 and PPV) in Michigan using Medicaid claims data between 2001 and 2008 revealed 72% of children with SCD received at least one pneumococcal vaccine by age 3 months and 73% had three documented by age 24 months. 21 These rates are similar to the 73.6% observed in this study. Lower rates of PPV adherence were seen in a retrospective cohort of Wisconsin Medicaid claims conducted between 2003 and 2007, with only 49.8% of children aged 2–18 years adherent with PPV vaccination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A case-control study of pneumococcal vaccine adherence (PCV7 and PPV) in Michigan using Medicaid claims data between 2001 and 2008 revealed 72% of children with SCD received at least one pneumococcal vaccine by age 3 months and 73% had three documented by age 24 months. 21 These rates are similar to the 73.6% observed in this study. Lower rates of PPV adherence were seen in a retrospective cohort of Wisconsin Medicaid claims conducted between 2003 and 2007, with only 49.8% of children aged 2–18 years adherent with PPV vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…1113 Despite this decline, few studies have monitored adherence to vaccination rates. 5,21,22 This study found 73.6% of children received their first PPV at age 2 years. A case-control study of pneumococcal vaccine adherence (PCV7 and PPV) in Michigan using Medicaid claims data between 2001 and 2008 revealed 72% of children with SCD received at least one pneumococcal vaccine by age 3 months and 73% had three documented by age 24 months.…”
Section: Discussionmentioning
confidence: 61%
“…Although children with sickle cell anemia had higher vaccination coverage, up to 45% were still not adequately vaccinated against IPD by 16 months of age. This is slightly lower than previously reported; however, our assessment of PPSV coverage, as well as the indication that children with sickle cell anemia were covered at a higher rate than children without sickle cell disease, are reflective of other findings . Given the significant room for improvement among this particularly vulnerable population, strategies that specifically target this subgroup of the population to increase vaccination coverage are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Rural counties were based on county of residence and HRSA standards for rural health grants [16], which provides identification of rural tracts within metropolitan counties. For this study, outreach clinics were considered as rural since !75% of patients followed in these clinics reside in a county classified as rural and the local GRU clinic was considered as urban since !75% of patients followed in this clinic reside in a county not classified as rural.…”
Section: Methodsmentioning
confidence: 99%